Micronutrient and Glucose-Related Biomarkers Until 24 Mo of Age in Infants Receiving Formula With Added Bovine Milk Fat Globule Membrane Through the First Year of Life: An RCT. (7th June 2021) - Jaramillo-Ospina, Angela; Toro-Campos, Rosario; Murguia-Peniche, Teresa; Wampler, Jennifer; Wu, Steven; Berseth, Carol Lynn; Uauy, Ricardo
Abstract: Objectives: Bovine milk fat globule membrane (bMFGM) added in routine infant formula supports normal growth and safety through 24 mo of age in term infants. The impact on micronutrients and glucose-related biomarkers is assessed here. Methods: In this double-blind, randomized, controlled trial, formula-fed infants were enrolled (<120 days of age) and randomized to receive a standard cow´s milk-based infant formula (SF, n = 174) or a similar formula with added whey protein-lipid concentrate (5 g/L; bMFGM; EF n = 173); exclusively breastfed infants were enrolled as a reference (HM, n = 235). In 50% of infants (chosen at random), parents agreed to blood collection (2–4 h fasting) at baseline, 6, 12, and 24 mo of age. Serum micronutrients (zinc, iron, ferritin, transferrin receptor) and glucose-related biomarkers (glucose, insulin, HOMA-IR [Homeostatic Model Assessment-Insulin Resistance], IGF-1) were analyzed. Results: At baseline, significant differences in markers of iron status (serum iron, ferritin) and glucose-related biomarkers (glucose, HOMA-IR, and IGF-1) were detected between HM and study formula groups. At 6 and 12 mo, no differences in any measure were detected between study formula groups. Serum iron and ferritin at 12 mo as well as glucose-related biomarkers at 6 mo (insulin, HOMA-IR, IGF-1) and 12 mo (IGF-1 only) were lower in the HM vs study formula groups. By 24 mo, micronutrients and glucose-related biomarkers were similar between study formula groups (with the exception of significantly lower serum iron in the SF group); for HM vs study formula groups, differences included significantly lower zinc and IGF-1. Conclusions: Patterns of micronutrients and glucose-related biomarkers were similar through two years of age in infants who received formula through one year. This study add to the body of data available for glucose-related biomarkers in children at two years of age and younger. Funding Sources: The study was funded by Mead Johnson Nutrition (MJN). TMP, SSW, and JLW are currently, and CLB was previously employed by MJN.